Survey and analysis long term deflection of cantilever bridge in Vietnam. Issue 1 (1st October 2022) - Nguyen, Duy Tien; Nguyen, Xuan Tung; Ngo, Van Minh
Abstract : The deflection and camber of bridge, especially of the box girder bridge as well as their effected factors have been important research topics since the end of the last century. In Vietnam, the box girder bridge constructed by cantilever method had been introduced since the 1990s and become popular in the last twenty years. After more than two decades of exploitation, these bridges face various problems such as over deflection, cracks... To clarify the actual deflection of the cantilevered box girder bridge and the effected factors such as creep and shinkage, the survey of long-term deflection of such box girder bridge (Hung Ha bridge) has been carried out and compare with the numerical analysis. The results show the significant effect of creep and shinkage to the long-term deflection of the cantilevered box girder bridge.